The Effect of Social Capital, Social Support, Self-Compassion, and Hope Factors Affecting Quality of Life of Breast Cancer Survivors: A Path Analysis Evidence from Surakarta, Central Java - Eka Miftakhul Jannah; Didik Gunawan Tamtomo; Bhisma Murti (Journal of Epidemiology and Public Health, 2020)
Background: Breast cancer is one of the most common cancers among women in the world. The study aims to analyze the effect of social capital, social sup